Working with Recently Arrived Horn of Africa Youth: An Intercultural Partnership Approach to Community Cultural Development - Clark, Sue; Gilmour, Jane (Culture and Local Governance / Culture et gouvernance locale)

(untitled) (Centre d'étude en gouvernance, Université d'Ottawa, 2011)
This paper documents and evaluates an intercultural arts partnership program that was directed towards improving settlement outcomes for Horn of Africa youth recently arrived in Melbourne, Australia. The paper presents the conceptual framework within which this program was developed. It examines the processes used in the project and evaluates the outcomes based on interviews and observations. It presents a model for individual and community development through the arts that is based on a collaborative approach that empowers young people to take responsibility. It argues for sustained interventions, based on principles of cultural empowerment, leadership development, and intercultural understanding, in order to maximize the capacity of young people – previously marginalized and disempowered – to contribute to the social sustainability of the communities in which they live.